Documenting Praise Names Ahanoŋkɔ Among Ewes: A Socio-Semantic Perspective - Yegblemenawo, Doreen Enyonam Esi; Yegblemenawo, Stella Afi Makafui (My University, 2021)
Names generally identify an individual and set him/her apart from other individuals. The Ewe (ISO639-3 [ewe])-speaking people of Ghana are known to have names which reflect an idea that a name giver or name bearer intends to put across. These names could be given due to, among others, circumstances under which the bearer was born, the day of birth, order of birth, or religious affiliations. Using a multifaceted approach in language documentation, this study focuses on a type of personal names termed ahanoŋkɔ (which literally translates as ‘drinking name’ or ‘name used while drinking alcohol’) among the Ewe of southeast Ghana, and investigates the semantic perspective of these praise names; ahanoŋkɔwo, as well as their social impact on the bearers and non-bearers of the names.
Keywords: praise names ahanoŋkɔ; Names; Ewes